Evolution of severe (transfusion‐dependent) anaemia in myelodysplastic syndromes with 5q deletion is characterized by a macrophage‐associated failure of the eythropoietic niche. (1st April 2022) - Buesche, Guntram; Teoman, Huesniye; Schneider, Rebekka K.; Ribezzo, Flavia; Ebert, Benjamin L.; Giagounidis, Aristoteles; Göhring, Gudrun; Schlegelberger, Brigitte; Bock, Oliver; Ganser, Arnold; Aul, Carlo; Germing, Ulrich; et al.
Summary: Evolution of erythrocyte transfusion‐dependent (RBC‐TD) anaemia associated with haploinsufficiency of the ribosomal protein subunit S14 gene ( RPS14 ) is a characteristic complication of myelodysplastic syndromes (MDS) with del(5q) [MDS.del(5q)]. Evaluating 39 patients with MDS.del(5q), <5% of anaemia progression was attributable to RPS14 ‐dependent alterations of normoblasts, pro‐erythroblasts, or CD34 + CD71 + precursors. Ninety‐three percent of anaemia progression and 70% of the absolute decline in peripheral blood Hb value were attributable to disappearance of erythroblastic islands (Ery‐Is). Ery‐Is loss occurred independently of blast excess, TP53 mutation, additional chromosome aberrations and RPS14 ‐dependent alterations of normoblasts and pro‐erythroblasts. It was associated with RPS14 ‐dependent intrinsic (S100A8 + ) and extrinsic [tumour necrosis factor α (TNF‐α)‐overproduction] alterations of (CD169 + ) marrow macrophages ( p  < 0.00005). In a mouse model of RPS14 haploinsufficiency, Ery‐Is disappeared to a similar degree: approximately 70% of Ery‐Is loss was related to RPS14 ‐dependent S100A8 overexpression of marrow macrophages, less than 20% to that of CD71 high Ter119 − immature precursors, and less than 5% to S100A8/p53 overexpression of normoblasts or pro‐erythroblasts. Marked Ery‐Is loss predicted reduced efficacy (erythrocyte transfusion independence) of lenalidomide therapy ( p  = 0.0006). Thus, erythroid hypoplasia, a characteristic complication of MDS.del(5q), seems to result primarily from a macrophage‐associated failure of the erythropoietic niche markedly reducing the productive capacity of erythropoiesis as the leading factor in anaemia progression and evolution of RBC‐TD in MDS.del(5q).